PENGARUH PENDIDIKAN FORMAL ORANG TUA DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM PESERTA DIDIK MTS PONPES AL-HASANAH BENGKULU TENGAH - Yulia Refyani (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2018)
The purpose of this writing is to know  the  influence  of formal education of parents  on learning  achievement, to know the influence of learning  motivation on learning  achievement and  to know the influence of formal education of parents and  learning motivation on learning achievement of Islamic education students  of MTs Ponpes Al-Hasanah Bengkulu Tengah. The method used in this research  is quantitative research  method, This research  type is non experimental quantitative research. Techniques of collecting research  data through  questionnaires, interviews, observations, and documentation. The data analysis techniques in this study by using multiple linear regression  analysis with the help of computer program SPSS version of Win- dows 16.0. The results of this study indicate that there is influence between  formal parent  education and learning motivation on learning achievement of Islamic religious education students of MTs Ponpes Al-Hasanah Central Bengkulu. The influence of for- mal education of parents  on learning achievement of Islamic religious education students  of MTs Ponpes Al-Hasanah Bengkulu The middle is 7.8%, while the remaining 92.2%  is influenced  by other variables other than the formal education of the parents. Furthermore there is a significant influence between  learning motivation on learning achievement of Islamic religious education students of MTs Ponpes Al-Hasanah Central Bengkulu. The influence of learning motivation on learning achievement of Islamic religious education in MTs Ponpes Al-Hasanah Bengkulu Tengah  is 27,3%,  while the rest 72,7%  is influenced  by other variable beside  motivation variable.  Influence  of parent  formal  education and  learning  motivation together  learning  achievement  of Islamic education student  of MTs Ponpes Al-Hasanah Bengkulu Tengah  is equal to 34,7%  while the rest is 65,3%  influenced  by other variable  besides formal education variable  of parent  and motivation to learn.